2006
DOI: 10.1007/s11284-006-0039-3
|View full text |Cite
|
Sign up to set email alerts
|

International Biodiversity Observation Year in Western‐Pacific and Asian regions (DIWPA‐IBOY): a case report on species rarity and spatio‐temporal variability of species composition in Lepidoptera and Coleoptera communities from a temperate forest of northern Japan

Abstract: An international project, DIWPA‐IBOY, took place for simultaneously observing biodiversity throughout the Western‐Pacific and Asian regions in 2001–2003, as one of the core projects for International Biodiversity Observation Year, a crosscutting network activity of DIVERSITAS (an international programme of biodiversity science). DIWPA‐IBOY provides extensive data on species diversity obtained by the standardized method. Under this project, 51,742 individuals of Lepidoptera and 11,633 of Coleoptera were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Holyoak et al (1997) demonstrated that the sampling efficiency of light traps depended on a series of meteorological conditions. When the habitat preferences in months were examined, 394 lepidopteran species (44.2%) and 14 coleopteran species (3.9%) favoured particular months, which suggests that the lepidopteran community turned over more rapidly than the coleopteran community ( Hirao et al , 2006 ). Using the same data set as this study, Hirao et al (in press) found that the number of trapped individuals and species of Coleoptera increased every day, but that the abundance and species richness of collected Lepidoptera were constant through the three sampling days in each month.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Holyoak et al (1997) demonstrated that the sampling efficiency of light traps depended on a series of meteorological conditions. When the habitat preferences in months were examined, 394 lepidopteran species (44.2%) and 14 coleopteran species (3.9%) favoured particular months, which suggests that the lepidopteran community turned over more rapidly than the coleopteran community ( Hirao et al , 2006 ). Using the same data set as this study, Hirao et al (in press) found that the number of trapped individuals and species of Coleoptera increased every day, but that the abundance and species richness of collected Lepidoptera were constant through the three sampling days in each month.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, therefore, the biased emergence of four lepidopteran species may have been caused by meteorological factors such as changes in the minimum temperature, although the effect of changing weather was minimised in the present study. Hirao et al (2006) suggested that this phenomenon is an effect of the differences between Lepidoptera and Coleoptera in the lifespan of adult individuals on the beta diversity among months. The daily species turnover of Coleoptera may reflect the behaviour of the beetles.…”
Section: Discussionmentioning
confidence: 99%
“…4) show that species composition changed greatly between successive months. In a deciduous broadleaved forest in central Hokkaido, Hirao et al (2006) also found that species composition of adult moth communities was distinctly partitioned into each month. These high species turnovers were due to the short occurrence period (1.8 months on average in the present study) of each species.…”
Section: Discussionmentioning
confidence: 81%
“…The peak abundance in autumn is probably caused by some dominant species that were extremely abundant that autumn (Yoshida 1980). Hirao et al (2006) collected adult moths in a deciduous broadleaved forest at the same locality as Yoshida (1980) and reported that July possessed the highest number of species and individuals. These studies suggest that a unimodal seasonal pattern with a peak in summer (July or August) is a general trend for species richness and abundance in adult moth assemblages in the cool-temperate region of central Hokkaido.…”
Section: Discussionmentioning
confidence: 99%
“…Although the overall awareness of the importance of biodiversity has recently increased while the emphasis in universities on taxonomy has decreased, the participants nevertheless emphasized the importance of the study of biodiversity, not only from an academic standpoint but also from the viewpoint of everyday life. As part of their Japanese case study on DIWPA-IBOY, Hirao et al (2006) presented a summary of the distribution of Lepidoptera and Coleoptera communities in Japan. The monitoring of ecosystem changes, as well as the research on the same topic, is characterized by its long-term nature and its focus on changes in the spatial distribution of ecosystems.…”
Section: Biodiversity In Human Lifementioning
confidence: 99%